Marketing of library and information services in university libraries: A case study of University of Malaya Central Library, Kuala Lumpur, Malaysia - Siti Juryiah, Mohd Khalid (2019)
Marketing and promotion play a very vital role in creating awareness for library and information products and services This topic discusses the importance of marketing and promotion in academic libraries with particular reference to Central Library, University of Malaya, Kuala Lumpur University libraries are established to provide information resources and services in order to support the purpose of the university. There are two research questions of the study. What are the types of information resources that are available in the Central Library? And the other one is what the marketing strategies are used by the Central Library. The objectives of the study are to identify the available Information resources and services in the Central Library and to unveil the strategies used by Central Library in marketing its resources and services. The reports Included marketing strategies employed by Central Library in promoting and attracting more library clientele as well as keeping them for long in the library. The paper concludes by advising librarians to promote their libraries through exhibitions and displays, publicity and public relations.